Flexibility of Al-Ijarah Contract Perspective of Islamic Economic Law - Mugni Muhit; Sofyan Al-Hakim UIN; Iwan Setiawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islam became a new form of authority in the 7th century after the fall of the Roman empire. The fall and destruction of this civilization was followed by the emergence and growth of various new civilizations that were just as impressive and proud. Other fields of life, including Islamic economics, are also developing simultaneously in line with culture, science and technology. Historical facts show that Islam is a comprehensive system of life that regulates all dimensions of life, including Islamic law (Islamic law), social, economic and political, and all aspects of spiritual life. According to the study of the history of Islamic law, from the time of the Prophet until the death of the Prophet Muhammad. there is no sharia problem in society that cannot be solved. This is because whenever a problem arises with sharia (Islamic law), its resolution is always left to the authority of the Prophet Muhammad who has received divine guidance from Allah Swt. Directly. Rasulullah Saw. has many legal precedents. The Companions said this clearly at the time and the Qur'an did not explain it.